Quantitative trait loci mapping reveals pleiotropic effect for grain iron and zinc concentrations in wheat. (29th February 2016) - Crespo‐Herrera, L.A.; Velu, G.; Singh, R.P.
Abstract: Malnutrition because of the deficiency of minerals such as iron (Fe) and zinc (Zn) afflicts over 2 billion people worldwide. Wheat is a major staple crop, providing 20% of dietary energy and protein consumption worldwide. Breeding wheat with elevated levels of grain Zn and Fe concentrations (GZn and GFe) represents a significant opportunity to increase the intake of these micronutrients for the resource poor people who depend on it as a major source of dietary energy. Synthetic hexaploid wheats (SHWs) have large genetic variation for GZn and GFe, which can be exploited for developing wheat varieties with higher concentrations of these minerals. The objective of this study was to localise genomic regions associated with GZn and GFe, thousand kernel weight (TKW) and test weight (TW) in a mapping population derived from the cross of Seri M82 and the SHW CWI76364. Major quantitative trait loci (QTL) on chromosome 4BS were detected for GZn and GFe; the QTL explained up to 19.6% of the total phenotypic variation for GZn and showed pleiotropic effects on GFe. This indicates that simultaneous improvement of GZn and GFe is feasible. Three and five QTL for TW and TKW were detected, respectively. One of the QTL for TKW was also located on chromosome 4BS. Positive correlations between plant height and GZn/GFe were observed. The 4BS QTL is of great interest for breeding biofortified wheat by means of marker‐assisted selection.